Conservation genomics: adaptation and gene flow - Höglund, Jacob (Henry Stewart Talks, 2023)
Conservation genomics, Adaptation and gene flow, Environmental change is ubiquitous, Selection and evolution, Genetic variation in large and small populations, The extinction vortex, Mutation, selection, and drift in large and small populations, Purging and genetic load, Local adaptation, Genetic rescue vs. outbreeding depression